2018
DOI: 10.1007/s10072-018-3566-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole body vibration and treadmill training in Parkinson’s disease rehabilitation: effects on energy cost and recovery phases

Abstract: The WBVT does not appear to require a long time of recovery and leads to less feeling of fatigue, whereas AER needs an appropriate recovery time after the training session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 41 publications
0
20
0
7
Order By: Relevance
“…Consequently, nine studies were included in the review: one was a non-randomized controlled pilot study 14 and eight were randomized controlled trials. [15][16][17][18][19][20][21][22] Figure 1 represents the findings of the search.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, nine studies were included in the review: one was a non-randomized controlled pilot study 14 and eight were randomized controlled trials. [15][16][17][18][19][20][21][22] Figure 1 represents the findings of the search.…”
Section: Resultsmentioning
confidence: 99%
“…overground, treadmill walking, and stationary cycling) in PwP was reported to improve _ VO 2peak, 14,15 decrease breathlessness, 16 increase maximum workload tolerated, 14 reduce BP, 17 and increase test duration of the CPET. 17,18 However, two studies reported a decrease, rather than an increase, in _ VO 2peak after aerobic training, 16,19 and one study reported no significant differences between the exercise group and the usual activity group.…”
Section: Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…The effect of whole body vibration on tremor is less prominent [87]. Moreover, it also does not appear to lead to better cardiovascular conditions reducing the feeling of fatigue when compared to treadmill training [89].…”
Section: Whole Body Vibrationmentioning
confidence: 98%